Student perceptions of remote access simulated learning in computed tomography. Issue 7 (2nd October 2020) - Liley, Tara; Ryan, Elaine; Lee, Kristal; Dimmock, Matthew; Robinson, John; Lewis, Sarah J.
ABSTRACT: National professional capabilities for Australian Diagnostic Radiography (DR) graduates require computed tomography (CT) scanning competence. Clinical placements have varied success in achiveing CT learning experiences and dedicated simulation at university can aid development of clinical skills. This study explored DR undergraduate students' attitudes, confidence and experiences of using a remote access simulation facility equipped with a live radiation commercial scanner. A pre- and post-clinical placement survey, with Likert scales and open-ended questions, was employed. Students in their third year of study undertook formal simulation CT learning using the NETRAD CT facility, prior to a four week off-campus clinical placement. Results indicate students (pre n = 21; post n = 23) had mixed levels of satisfaction when using NETRAD CT even though learning outcomes and relevance was clear. Comparison of pre- and post-matched statements reveals a significant decrease in students' perception of confidence in their skills post-clinical placement, reduced satisfaction with remote learning and increased preference for hands-on experiences. Open-ended responses were polarised to either positive simulation themes of convenience and repeatability, alongside negative themes with remote access and lack of facilitation. While students considered CT simulation to be educationally engaging, the technology-rich learning environment presented challenges and believed interactive simulation is inferior to real clinical experiences.